2022
DOI: 10.1039/d2nj02175g
|View full text |Cite
|
Sign up to set email alerts
|

Cu3N nanoparticles with both (100) and (111) facets for enhancing the selectivity and activity of CO2 electroreduction to ethylene

Abstract: CO2 electroreduction to high value-added chemicals is a prospective approach to realize the utilization of CO2 resources and mitigate the greenhouse effect. Ethylene (C2H4), as an important chemical materials, is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…They are a class of interstitial compounds in which the nitrogen atoms are integrated into the interstitial sites of the parent metals resulting in possessing exceptional properties such as high electrical conductivity, chemical stability, electrocatalytic activity, and mechanical robustness . Recently, TMNs have received much attention in electrocatalytic applications, including oxygen evolution/reduction reaction (OER/ORR), , hydrogen evolution/oxidation reaction (HER/HOR), , and nitrogen fixation reactions. , However, TMNs are relatively a new class of materials for CO 2 RR and less attention has been paid to their applications in CO 2 RR. , Wang et al recently reported high CO 2 RR selectivity to C 2 H 4 at −0.8 V (vs reversible hydrogen electrode (RHE)) with a Faradaic efficiency of 61.1% using Cu 3 N nanoparticles as catalysts. Yin et al .…”
Section: Introductionmentioning
confidence: 99%
“…They are a class of interstitial compounds in which the nitrogen atoms are integrated into the interstitial sites of the parent metals resulting in possessing exceptional properties such as high electrical conductivity, chemical stability, electrocatalytic activity, and mechanical robustness . Recently, TMNs have received much attention in electrocatalytic applications, including oxygen evolution/reduction reaction (OER/ORR), , hydrogen evolution/oxidation reaction (HER/HOR), , and nitrogen fixation reactions. , However, TMNs are relatively a new class of materials for CO 2 RR and less attention has been paid to their applications in CO 2 RR. , Wang et al recently reported high CO 2 RR selectivity to C 2 H 4 at −0.8 V (vs reversible hydrogen electrode (RHE)) with a Faradaic efficiency of 61.1% using Cu 3 N nanoparticles as catalysts. Yin et al .…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of fossil fuels results in the annual release of significant amounts of carbon dioxide (CO 2 ) into the atmosphere, intensifying the greenhouse effect and ocean acidification. [1][2][3] On the other hand, CO 2 is also a bountiful carbon source widely present in the atmosphere. Using renewable clean energy, such as solar energy, to convert CO 2 into high value-added chemicals can promote the carbon cycle, which is helpful to solve the greenhouse effect and energy shortage.…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of fossil fuels results in the annual release of significant amounts of carbon dioxide (CO 2 ) into the atmosphere, intensifying the greenhouse effect and ocean acidification 1–3 . On the other hand, CO 2 is also a bountiful carbon source widely present in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…A shape anisotropic catalyst, which has exposed facets with different work functions, will naturally have excellent carrier separation driving force. 21–25 Under such internal electric field (IEF), photogenerated electron-hole pairs will be spatially separated on different crystal planes, suppressing surface recombination and more efficiently leading to a selective regional photoinduced reaction. 26–28 Some semiconductors were synthesized with this purpose.…”
Section: Introductionmentioning
confidence: 99%